2010
DOI: 10.1007/s00415-010-5486-7
|View full text |Cite
|
Sign up to set email alerts
|

Central pontine and extrapontine myelinolysis: from epileptic and other manifestations to cognitive prognosis

Abstract: The objective of this study is to review the presentation, outcome and aetiology of central pontine and extrapontine myelinolysis (CPEPM) in a tertiary hospital center. The study method is a case series and included identification of patients from University of Montreal Health Centre archives database (1995-2007). All diagnoses were confirmed by neuroimaging or brain autopsy. Twelve individuals (25-66 years old) presented heterogeneous manifestations. Co-morbidities included diabetes insipidus (n = 2), haemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 21 publications
(27 reference statements)
2
41
1
4
Order By: Relevance
“…We found 54 cases (63% female, median age 45 years, interquartile range 45-58 years) of osmotic demyelination syndrome published since 1997: 45 individual case reports and three case series including a total of nine patients (72,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175). In 96% (52/54), the diagnosis of osmotic demyelination syndrome was based on magnetic...…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…We found 54 cases (63% female, median age 45 years, interquartile range 45-58 years) of osmotic demyelination syndrome published since 1997: 45 individual case reports and three case series including a total of nine patients (72,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175). In 96% (52/54), the diagnosis of osmotic demyelination syndrome was based on magnetic...…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Gocht et al [2] examined lesion distribution in 58 autopsy cases with OM and found cerebral corticosubcortical lesions in 15%. To the best of our knowledge, corticosubcortical lesions associated with OM have been unfamiliar clinically, and their imaging findings have been reported only sporadically [4][5][6][7][8][9]. Okeda et al [3] studied the pathological features of corticosubcortical lesions in autopsy cases with OM and reported two distinct subtypes of lesions: cortical and subcortical.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, MRI findings of OM consist primarily of hyperintensity on T 2 weighted images (T 2 WI) or fluid-attenuated inversion-recovery (FLAIR) images in the central pons (central-pontine myelinolysis), midbrain, bilateral thalami and/or basal ganglia (extrapontine myelinolysis), or a combination of these [1]. Although cerebral corticosubcortical involvements have been described in pathological studies [1][2][3], a description of the MRI findings has been mostly limited to case reports [4][5][6][7][8].We report serial MRI findings in two patients with corticosubcortical lesions associated with OM. One patient's lesions were disclosed on MRI that included diffusion-weighted imaging (DWI) and T 1 weighted imaging (T 1 WI) with contrast enhancement that were obtained 8 days (late acute phase) and 26 days (subacute phase) after the onset of neurological symptoms.…”
mentioning
confidence: 99%
“…The classical symptoms of myelinolysis are spastic quadriparesia and pseudobulbar paralysis, which The frequently observed symptoms of this disorder include acute para-or quadriparesis, dysphagia, dysarthria, diplopia, loss of consciousness, and other neurological symptoms associated with brainstem damage [7,8]. Our patient presented with tetraparesis that progressed to pseudobulbar paralysis and inability to breathe.…”
Section: Discussionmentioning
confidence: 75%